General and Special Techniques of Mediation - Kertész, Tibor (Interdisciplinary and Child-Friendly Communication, 2025)
This chapter explores the fundamental and specialized techniques mediators employ to facilitate constructive conflict resolution, focusing particularly on the principles of transformative mediation. Emphasizing self-determination, empowerment, and mutual recognition, it presents mediation as a process that enables parties to remain owners of their conflicts while enhancing their communication and understanding. The text distinguishes between general techniques –such as active listening, questioning, paraphrasing, reframing, summarizing, and recognition – which are essential in all mediation processes, and special techniques – such as caucusing, venting, mirroring, storytelling, and silence – that are used selectively based on contextual and methodological considerations. Each method is explained with practical examples, highlighting the mediator’s skill in choosing and applying them appropriately. By integrating these approaches, the chapter provides a comprehensive framework that supports mediators in promoting clarity, empathy, and cooperation, ultimately leading to sustainable, mutually satisfactory agreements rooted in transformative practice.Keywords: Mediation Theory, Transformative Mediation, Conflict Resolution Processes, Dispute Resolution, Communication Strategies, Facilitative Mediation, Emotional Regulation, Mediator Skills, Questioning Techniques, Active Listening, Paraphrasing, Neutral Reframing, Summarising Techniques, Recognition in Mediation, Reality Testing, Caucusing, Feedback Methods, Storytelling in Mediation, Empowerment, Self-Determination